2011
DOI: 10.3390/su3020424
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Reference Values in Indicator-Based Methods for the Environmental Assessment of Agricultural Systems

Abstract: Many indicator-based methods for the environmental assessment of farming systems have been developed. It is not the absolute values of the indicators that reveal whether the impact of a system is acceptable, but rather the distance between these values and some reference values. We reviewed eight frameworks for the environmental assessment of agricultural systems that define reference values for their indicators. We analyzed the methods used to establish reference values and explored how to improve these metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…"Normative reference values are defined based on science or policy (Experts and stakeholders may be involved), whereas relative reference values are based on indicator values for similar systems or a reference/ideal system. Normative reference values allow comparison of a system with previously defined reference values" [33] (p. 433). To produce a sustainability assessment which is robust, comparable, and transparent among stakeholders, it is important to clarify what type of reference point is being used in the sustainability assessment, as well as how the reference points were determined and why [33].…”
Section: Elimination Methods Of Mcdamentioning
confidence: 99%
See 2 more Smart Citations
“…"Normative reference values are defined based on science or policy (Experts and stakeholders may be involved), whereas relative reference values are based on indicator values for similar systems or a reference/ideal system. Normative reference values allow comparison of a system with previously defined reference values" [33] (p. 433). To produce a sustainability assessment which is robust, comparable, and transparent among stakeholders, it is important to clarify what type of reference point is being used in the sustainability assessment, as well as how the reference points were determined and why [33].…”
Section: Elimination Methods Of Mcdamentioning
confidence: 99%
“…Normative reference values allow comparison of a system with previously defined reference values" [33] (p. 433). To produce a sustainability assessment which is robust, comparable, and transparent among stakeholders, it is important to clarify what type of reference point is being used in the sustainability assessment, as well as how the reference points were determined and why [33]. In the current study, relative reference values are used.…”
Section: Elimination Methods Of Mcdamentioning
confidence: 99%
See 1 more Smart Citation
“…It is remarkable that most methods for the assessment of agricultural sustainability (Acosta-Alba and Van der Werf, 2011;van der Werf et al, 2007;Van Passel and Meul, 2011), fall within the category of composite indicators. The sustainability analysis touches upon very diverse range of aspects that cannot be aggregated without having to turn to composite metrics in the end.…”
Section: Measure Determination and Aggregation Across Different Dimenmentioning
confidence: 99%
“…An overview of available tools was established using the search engine Scopus and the snowball method. The following list of reviews and scientific papers on sustainability assessments were identified through a literature study (Acosta-Alba and Van Der Werf, 2011;Binder et al, 2010;FAO, 2013a;Galan et al, 2007;Halberg et al, 2005;Marchand et al, 2012;Marta-Costa and Silva, 2013;Schader et al, 2014;Van Cauwenbergh et al, 2007;Van Der Werf et al, 2007;Van Passel and Meul, 2012). In addition, several recently developed tools that were presented at scientific conferences were added to the list and the developers were contacted to discuss the characteristics of the tools.…”
Section: Overview Of Sustainability Assessment Toolsmentioning
confidence: 99%